Migration Of Health/Social Workers From Zimbabwe To The United Kingdom: Prospects And Challenges - Chipatiso, Ezra; Nhondo, Benonia Tanatswa (My University, 2023)
Recent decades have witnessed the mass movement of social and health workers from Sub-Saharan Africa, particularly Zimbabwe, to the United Kingdom (UK). This study focused on the development of social work in Zimbabwe, which, like in other African countries, has been attributed to colonial roots. The role of social worker through advocacy on behalf of people living with HIV/AIDS and vulnerable groups, has been spelt out. By employing a qualitative approach using questionnaires and interview guides, this study explored the factors contributing to the migration of social worker to the United Kingdom (UK). Participants indicated high costs of living, political instability, poor health services and costly health care as the main reasons for migration of Zimbabwean social workers to the UK. Improved standard of living, improved health care, competitive income and favourable political climate, were noted as the factors which have attracted the mass movement of social and health workers from Zimbabwe to the UK. However, the study revealed that some social workers who intend to migrate to UK were not aware of the risks associated with immigrants.
Keywords: SOCIAL SCIENCES::Social sciences::Social work; Push Factors; Community Development